Effect of Activated Carbon and ZSM-5 on Oil Yield from Microwave Assisted Pyrolysis of Automotive Paint Sludge (APS) - Ariff Za’bar, Johan; Abd Rahman, Norazah; Januri, Zakiuddin; Nor Faizah, Syarifah; Shawalliah Idris, Siti (International Journal of Engineering and Technology, 2018)
Automotive paint sludge (APS) contains valuable material which can be recovered by microwave-assisted pyrolysis as studied by previous researches. In this study, a combined application of microwave absorber and catalyst is used in order to study the effect of both components in microwave-assisted pyrolysis of APS. Activated carbon and ZSM-5 acted as microwave absorber and catalyst, respectively were used to investigate their effect on pyrolytic oil produced from APS. Parameters used were microwave power (W), radiation time (T), amount of microwave absorber and amount of catalyst. It was observed that catalyst of 1.5% yielded the highest amount of oil product, which is 1.84% when mass loading, power, time and MWA are fixed. Meanwhile, MWA of 6% produced the highest amount of oil product, which is 7.75% when mass loading, power, time and catalyst are constant. On the other hand, the calorific value (CV) for oil products is found to be in the range of 37 MJ/kg to 39 MJ/kg, which is within the range of commercialized liquid fuel of 36 MJ/kg to 48 MJ/kg. The outcome of this work is beneficial for the alternative utilization of APS particularly as renewable fuel.Â